Onomasiological cyclicity in the expression of concessive relations - Longhin, Sanderleia Roberta [UNESP] (Ubiquity Press Ltd, 2022)
In this paper, I discuss processes of language change which have led to the constitution of concessive connectives in two genetically related languages, Latin and Portuguese. I focus on the diachronic developments of the Latin licet, and of bem que and embora, from Portuguese, whose sources are etymologically different: the modal verb licere, the emphatic adverb bem and the volitive adverbial phrase em boa hora. The main purpose is to investigate whether the three phenomena could be taken as stages of an onomasiological cycle of a semanticpragmatic nature, as proposed by Hansen (2018). Based on studies in Latin linguistics about licet and on the analysis of the grammaticalization processes for bem que and embora in an interactional diachronic sample, I shall argue that, in the three instances of evolution, there has been a stage in which licet, bem and embora have acted as assent markers, and that this usage, in combination with contextual traits, has been crucial to sustain the inferential processes which enabled the concessive interpretation. The similar source and target meanings and the continuity of inferential processes over time also suggest that this is a recurrent path of renewal of the concessive meaning which displays a cyclicity pattern.